Vulnerabilidade socioambiental a extremos climáticos de secas em ilhas do reservatório da usina hidrelétrica de Balbina - Presidente Figueiredo (AM). - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Episodes of extreme weather events have been occurring more frequently in recent years, which makes the affected human populations even more vulnerable at each cycle of these events’ occurrence. And, to the riverside people who live on the islands of the communities (Boa União and Novo Rumo) that are located inside the reservoir of the Balbina Hydroelectric Power Plant– Presidente Figueiredo (AM) It has not been different. Farmers and fishermen who develop their productive activities on the islands try to adapt to the environment that was formed after the construction of the plant, however, extreme drought events make this process of adaptability quite difficult, making these populations even more vulnerable to these impacts. Therefore, the objective of this research was to carry out an analysis of the socio-environmental vulnerabilities of human populations that live and/or produce on the islands of the Balbina hydroelectric plant reservoir in the face of extreme drought events. The study was developed from a methodological perspective considered exploratory-descriptive, being the qualitative method. Data collection was carried out through forms with semi-structured interviews using the Kobo Toolbox program, whereby it was possible to obtain reports, graphs and tables after collecting the information. The thesis results are divided into three chapters. The first chapter aimed to present the socio-environmental history in the periods: before, during and after the implementation of the Balbina Hydroelectric Power Plant, the results of the interviews showed how the impacts of the construction of the plant affected the environment and the human populations that lived there. The second chapter aimed to correlate the production of productive activities with the occurrence of extreme weather events on the islands of the Balbina reservoir, and according to the results it was noticed that the production of productive activities of agriculture and fishing are directly affected in the periods when climatic extremes occur. the objective of the third chapter was to estimate the socio-environmental vulnerabilities of the riverside people in the face of the process of adaptability to extreme drought events, the results of this chapter showed medium and high vulnerability of the human populations that live on the islands of the Balbina reservoir through access and sourcing of water resources, energy and food security as well.
Keywords: Extremos climáticos - Presidente Figueiredo (AM); Mudanças climáticas - Presidente Figueiredo (AM); Solos e clima; Trabalhadores rurais; CIENCIAS BIOLOGICAS: ECOLOGIA; CIENCIAS EXATAS E DA TERRA: GEOCIENCIAS: METEOROLOGIA: CLIMATOLOGIA; CIENCIAS EXATAS E DA TERRA: GEOCIENCIAS: GEOMORFOLOGIA: HIDROGEOGRAFIA; Vulnerabilidade; Eventos Extremos de Secas; Ribeirinhos; Ilhas; Reservatório de Balbina